Resident Perspectives on Palliative Care at an Urban Teaching Hospital. Issue 3 (July 2022) - Raman, Uma; Ebby, Cris G.; Ahmad, Seherisch; Mukherjee, Thayer; Yang, Ellen; Fofah, Onajovwe; Scolpino, Anthony J.; Oleske, James M.
Background: There has been an increasing need to address end of life (EOL) care and palliative care in an era when measures to extend life for terminal illnesses are often initiated without consideration of quality of life. Addressing the barriers for resident physicians to initiate EOL conversations with patients is an important step towards eliminating the disconnect between patient wishes and provider goals.Objective: To assess resident physician perspectives on initiating palliative care conversations with terminally ill patients at an urban teaching hospital.Methods: This paper solicited the experiences of pediatric, general surgery, and internal medicine residents through an anonymous survey to assess exposure to palliative care during training, comfort with providing palliative care, and barriers to implementing effective palliative care.Results: 45% of residents reported exposure to palliative care prior to medical training. Ninety-three percent of these residents reported being formally introduced to palliative care during medical training through formal lecture, although the majority reported also being exposed through either small group discussions or informal teaching sessions. Time constraints and lack of knowledge on how to initiate and continue conversations surrounding EOL care were the greatest barriers to effectively caring for patients with terminal illnesses. Residents concurred that either attending physicians or hospital-designated palliative care providers should initiate palliative care discussions, with care managed by an interdisciplinary palliative care team; this consensus demonstrates a potential assumption that another provider will initiate EOL discussions.Conclusions: This study evaluated the current state of physician training in EOL care and provided support for the use of experience-based training as an important adjunct to traditional didactic lectures in physician education.